Human Competency Assessment for Software Configuration Management. Issue Volume 5:Number 5(2021)Special Issue (2021) - Fahmy, Syahrul; Deraman, Aziz; Yahaya, Jamaiah; Hamdan, Abdul Razak
No abstract available